A Three-Pole Substrate Integrated Waveguide Bandpass Filter Using New Coupling Scheme - Guan, Xuehui; Yuan, Ye; Liu, Haiwen; Huang, Wei (Společnost pro radioelektronické inženýrství, 2015)
A novel three-pole substrate integrated waveguide (SIW) bandpass filter (BPF) using new coupling scheme is proposed in this paper. Two high order degenerate modes (TE102 and TE201) of a square SIW cavity and a dominant mode (TE101) of a rectangular SIW cavity are coupled to form a three-pole SIW BPF. The coupling scheme of the structure is given and analyzed. Due to the coupling between two cavities, as well as the coupling between source and load, three transmission zeros are created in the stopband of the filter. The proposed three-pole SIW BPF is designed and fabricated. Good agreement between simulated and measured results verifies the validity of the design methodology well.
Keywords: Transmission zero; substrate integrated waveguide (SIW); degenerate mode; coupling matrix